Rumex bucephalophorus L. subsp. bucephalophorus en Andalucía. - Talavera Solís, María (Acta Botanica Malacitana, 2006)
Rumex bucephalophorus L. subsp. bucephalophorus in Andalusia. Palabras clave. Flora, corología, Rumex bucephalophorus, España. Key words. Flora, chorology, Rumex bucephalophorus, Spain.